Analisis Klasifikasi Kemampuan Kalkulus Mahasiswa Berdasarkan Gender Berdasarkan Skor Asesmen - Lalu Sucipto; Habibi Ratu Perwira Negara (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze and classify students’ calculus abilities and to examine differences in these abilities based on gender. The study employed a quantitative approach with a descriptive–comparative research design. The research subjects consisted of 104 students from four classes. The research instrument was a calculus essay test consisting of three items. Data analysis techniques included descriptive statistical analysis, classification of calculus ability into five categories, and testing for gender-based differences using an independent samples t-test, supported by the Mann–Whitney test. The results showed that students’ calculus abilities were predominantly in the low (39.42%) and moderate (35.58%) categories, while the high and very high categories accounted for only 13.46% and 11.54%, respectively, and no students were classified in the very low category. The findings indicate that students’ calculus abilities still need to be improved and are not significantly influenced by gender.